Differences between acoustic trauma and other types of acute noise-induced hearing loss in terms of treatment and hearing prognosis. (10th March 2017) - Wada, Tetsuro; Sano, Hajime; Nishio, Shin-ya; Kitoh, Ryosuke; Ikezono, Tetsuo; Iwasaki, Satoshi; Kaga, Kimitaka; Matsubara, Atsushi; Matsunaga, Tatsuo; Murata, Takaaki; Naito, Yasushi; Suzuki, Mikio; et al.
Abstract: Objectives: To evaluate the differences between acoustic trauma (AT) and other types of acute noise-induced hearing loss (ANIHL), we performed a literature search and case reviews. Methods: The literature search based on online databases was completed in September 2016. Articles on ANIHL and steroid treatment for human subjects were reviewed. The source sounds and treatment sequelae of our accumulated cases were also reviewed. Hearing loss caused by gun-shots and explosions was categorized into the AT group, while hearing loss caused by concerts and other noises was categorized into the ANIHL group. Results: Systemic steroid treatment did not appear to be effective, at least in the AT group, based on both the literature and our case reviews. However, effective recovery after treatment including steroids was observed in the ANIHL group. The difference in hearing recovery between the AT and ANIHL groups was statistically significant ( p  = .030), although differences in age, days from the onset to treatment and pretreatment hearing levels were not significant. Conclusions: Hearing recovery from AT is very poor, whereas, ANIHL is recoverable to some extent. Therefore, it is essential to differentiate between these two groups for accurate prediction of the hearing prognosis and evaluation of treatment effects.